Elucidating Divergent Growth and Climate Vulnerability in Abalone (Haliotis iris): A Multi-year Snapshot - Copedo, Joanna S; Webb, Stephen C; Delisle, Lizenn; Knight, Ben; Ragg, Norman LC; Laroche, Olivier; Venter, Leonie; Alfaro, Andrea C (Elsevier BV, 2025)
Many abalone populations worldwide are in decline as a result of changing climate and fishing pressure. In New Zealand (NZ) Haliotis iris is the largest and most abundant of the endemic abalone species. This species displays high levels of phenotypic variation with slow-growing populations having an impact on their commercial utilisation. The present study incorporates targeted histopathological approaches to characterise tissue-level factors in abalone from NZ's principal fishing region. Adult (n = 60) and sub-adult (n = 56) H. iris were collected from two Chatham Island sites that display differential growth rates; sampling was repeated on six occasions over three years. Through histology the slower-growing adult population was observed to have an elevated ceroid score, higher prevalence of kidney stones and increased prevalence of a plasmodia stage of haplosporidian-like parasites in the right kidney, when compared with the faster-growing and sub-adult populations. Furthermore, the faster-growing adult population appeared to be retaining mature oocytes over the predicted spawning season with higher-than-expected atresia (oocyte degeneration). Factors implicated in growth performance between the two populations include site, environment, parasites, pathology, reproduction, ceroid deposition and previously reported nutritional status. The 18S PCR and metabarcoding on the right kidney tissue were negative for haplosporidian/Urosporidium previously reported in H. iris, with metabarcoding results detecting an apicomplexan ancestral group. The reproductive, somatic and parasite findings from the current study provides critical information on abalone physiological condition which allows facilitation of early detection of conditions that may impact the sustainability and management of H. iris stocks in New Zealand under a changing climate. For instance, changes to reproductive condition may reduce oocyte quality and quantity thereby reducing recruitment to the next generation.
Keywords: Abalone; Atresia; Gametogenesis; Haliotis iris; Histopathology; Parasites; 31 Biological Sciences; 03 Chemical Sciences; 05 Environmental Sciences; 06 Biological Sciences; Marine Biology & Hydrobiology; 31 Biological sciences; 34 Chemical sciences; 41 Environmental sciences; Animals; Gastropoda; Climate Change; New Zealand; Reproduction